Aromaticity and Chemical Bonding of Chalcogen‐Bonded Capsules Featuring Enhanced Magnetic Anisotropy. Issue 19 (1st September 2020) - Tzeli, Demeter; Petsalakis, Ioannis D.; Theodorakopoulos, Giannoula; Rahman, Faiz‐Ur; Ballester, Pablo; Rebek, Julius; Yu, Yang
Abstract: We present a theoretical study of chalcogen bonded container capsules (AX +AX ) where X=O, S, Se, and Te, and their encapsulation complexes with n‐ C9 H20 ( n‐ C9 H20 @AX +AX ). Both Se and Te encapsulation complexes have significant experimental and computed binding energies, analogous to the hydrogen bonded counterparts, while the S and O capsules and their encapsulation complexes show only weak binding energies, which are attributed to different types of bonding: chalcogen S⋅⋅⋅N bonds for S‐capsules and π–π stacking and weak hydrogen bonds for the O case. All AX +AX and C9 H20 @AX +AX present unusually high magnetic anisotropies in their interiors. The 1 H NMR spectra of the encapsulation complexes display the proton signals of the encapsulated n‐ nonane highly upfield shifted, in agreement with the available experimental data for the Se capsule. We found that different factors contribute to the observed magnetic anisotropy of the capsule's interior: for the Te capsule the most important factor is Te's large polarizability; for the O analogue the inductive effects produced by the electronegative nature of the O and N heteroatoms; and for the S and Se capsules, the polarizability of the heteroatoms combines with electric field effects. Abstract : Under wraps : A theoretical study of chalcogen bonded container capsules (AX +AX ) and their encapsulation complexes with n‐ C9 H20 ( n‐ C9 H20 @AX +AX ) for X=O−Te is presented. Se and Te species were found to have significant binding energies (ΔE), while S and O species show weak ΔE attributed to different types of bonding. All capsules and encapsulation complexes present unusually high magnetic anisotropies in their interiors. The 1 H NMR chemical shift values of encapsulated n‐ nonane are significantly upfield shifted with respect to the free guest in all four capsules.